Apakah Emosi Negatif Dapat Berhubungan dengan Perilaku Positif di Tempat Kerja? Perilaku Shame-Proneness dan Customer Oriented-Organizational Citizenship pada Pegawai Negeri Sipil di Pekanbaru - Cucuani, Hijriyati; Sulastiana, Marina; Harding, Diana; Agustiani, Hendriati (CV. ITTC INDONESIA, 2023)
The shame belongs to negative emotions, which in many psychological studies are associated with negative behaviors. The discomfort that a person experiences when he feels shame is associated with the emergence of negative behavior. Indonesians, especially people in Pekanbaru City who are closely attached to the teachings of Islam, view Shame as a more positive. Feeling uncomfortable will make people control their behavior and avoid shameful behavior. This study investigated the correlation between shame-proneness and Customer Oriented-Organizational Citizenship Behavior (CO-OCB) on 331 civil servants from 15 Pekanbaru government instances randomly selected. Result suggest that shame-proneness has a positive relationship with CO-OCB (r = 233, p = 0.00). Compared to felt-shame, the dimension of anticipatory shame has a higher correlation coefficient with CO-OCB and its dimensions (helping behavior, sportsmanship, organization loyalty, organization compliance, individual initiative, and civic virtue) except self-development. Civil servants need to internalize the shame to violate the rules so that they tend to act according to the rules and provide the best for the organization in which they work.